Lucio Leprosy with Lucio's phenomenon, digital gangrene and anticardiolipin antibodies - Ortega Cabrera, L. (2017)
Lucio's phenomenon (LPh) is considered a necrotizing panvasculitis and a variant of leprosy Type 2 reaction, clinically characterised by necrotic-haemorrhagic lesions on the extremities and trunk. LPh is observed in diffuse lepromatous leprosy (DLL or Lucio-Latapi leprosy). This is a distinct form of lepromatous leprosy (LL) reported mainly in Mexico. Anti-phospholipid antibody syndrome (APS) has been rarely described in LPh. We report a case of Lucio-Latapi leprosy with LPh observed in a patient from the province of El Oro in Ecuador, who presented clinical manifestations of long standing DLL (non-nodular infiltration of the skin, collapse of the nasal pyramid, madarosis, atrophy of the earlobes), of LPh (necrotic-haemorrhagic macules with irregular shapes) and of APS (necrosis of the right big and second toe). Histopathology showed perineural and periadnexal foamy macrophages with numerous bacilli (diagnostic of LL) in the subcutis, a mild lobular panniculitis with a large subcutaneous vessel infiltrated by macrophages in the wall (typical of LPh) and vessels of the superficial and mid dermis occluded by thrombi but without signs of vasculitis (typical of occlusive vasculopathy as in APS). Our observations suggest that some cases of LPh may be associated with APS. Anticardiolipin antibodies (aCL) and lupus anticoagulant (LA) should be tested in patients with LPh because this may have therapeutic implications.